Comparison of the efficacy of LTCBDE and LCBDE for common bile duct stones: a systematic review and meta-analysis - Zheng, Bin; Lu, Yixin; Li, Erqi; Bai, Ziyu; Zhang, Kaiqian; Li, Jian (Frontiers in Surgery, 2025)
BackgroundThe choice of surgical methods for common bile duct stones (CBDS) is controversial. The aim of this study was to compare the safety and efficacy of laparoscopic transcystic common bile duct exploration (LTCBDE) and laparoscopic common bile duct exploration (LCBDE).MethodsRelevant literature published before March 30, 2023 in PubMed, Web of Science, Embase, and Cochrane was searched to screen studies comparing LTCBDE and LCBDE. RevMan 5.4 was used for meta-analysis of fixed-effects and random-effects models.ResultsA total of 21 studies met the inclusion criteria, including 3065 patients in the LTCBDE group and 2,453 patients in the LCBDE group. CBDS clearance was 95.4% (2,682/2,812) in LTCBDE group and 94.7% (1,810/1,911) in LCBDE group (OR: 1.84, 95% CI: 1.36, 2.48, P < 0.0001; I2 = 0%, P = 0.56). In LTCBDE group, operative time(MD = −34.60, 95% CI: −46.05, −23, 15, P < 0.00001 I2 = 96%, P < 0.00001), postoperative hospital stay (MD = −2.92, 95% CI: −3.62, −2.21, P < 0.00001; I2 = 92%, P < 0.00001), postoperative complications (OR: 0.47, 95% CI: 0.38, 0.58, P < 0.0001; I2 = 26%, P = 0.15), residual stone(OR: 0.48, 95% CI: 0.34, 0.66, P < 0.0001; I2 = 0%, P = 0.56), bile leak (OR: 0.37, 95% CI: 0.25, 0.55, P < 0.00001; I2 = 0%,P = 0.52), mortality (OR: 0.10, 95% CI: 0.01, 0.88, P = 0.04; I2 = 0%, P = 0.71) and recurrent stones(OR: 0.34, 95% CI: 0.15, 0.74, P = 0.007; I2 = 5%, P = 0.38) were better than LCBDE group. There was no difference in pancreatitis (OR: 1.06, 95% CI: 0.52, 2.16. P = 0.86; I2 = 0%, P = 0.98) and biliary stricture(OR: 0.30, 95% CI: 0.08, 1.09, P = 0.07; I2 = 0%, P = 0.57).ConclusionsLTCBDE is safe, efficient, and of great clinical significance, and is worth promoting to some patients.